Safety assessment of the substance nano precipitated calcium carbonate for use in plastic food contact materials. (23rd February 2022) - ,; Lambré, Claude; Barat Baviera, José Manuel; Bolognesi, Claudia; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Lampi, Evgenia; Mengelers, Marcel; Mortensen, Alicja; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the substance 'nano precipitated calcium carbonate', FCM substance No. 1087, the particles size of which is in the range of ■■■■■, with a median of ■■■■■. The substance is intended to be used as a filler in all plastics at up to 5% w/w for contact with acidic food and at up to 40% w/w for contact with all other types of food. Articles made with the substance are intended for long‐term storage at room temperature or below. The particulate form of the calcium carbonate dissolved rapidly under simulated gastric conditions and, therefore, in accordance with the EFSA Guidance on Particle – Technical Requirements (2021), an assessment of the particles in nanoform is not required and a conventional risk assessment is sufficient. Calcium carbonate, not in nanoform, is authorised for use in plastic FCM without specific migration limit (FCM No. 21) and for use as a food additive (E 170). Migration, from low‐density polyethylene (LDPE) containing 40% of the substance, was below 0.03 mg/kg in isooctane and 95% ethanol, and 5.4 mg/kg in 10% ethanol. For LDPE containing 5% of the substance, corresponding to the maximum intended amount for contact with acidic foods, the migration was 17 mg/kg. Therefore, the CEP Panel concluded that the substance nano precipitated calcium carbonate is not of safety concern for consumers when used as a filler in all types of polymer for all types of food, except for infant food formulae. The Panel noted, however, that for acidic foods, the overall migration limit may be exceeded.